Dislipidemia Aterogenik pada Pasien Diabetes Melitus Tipe 2: Patofisiologi dan Pilihan Terapi - Rosandi, Rulli (PT Dexa Medica, 2021)
Atherogenic dyslipidemia is characterized by increase in triglyceride and small dense lipoprotein (sdLDL) level and decrease in high-density lipoprotein (HDL) level. This condition is accompanied by increased TG-rich very-low-density lipoprotein, apolipoprotein B, and oxidized low-density lipoprotein (oxLDL). This lipid profile plays an important role in the pathogenesis of cardiovascular disorders such as coronary heart disease, peripheral artery disease, and stroke. Diabetes mellitus is an independent risk factor for premature atherosclerosis. High- and moderate-intensity statins are recommended therapeutic options in the management of this disorder. Currently, there are also some therapeutic options other than statin to accompany statin therapy. Ezetimibe and proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitor are mentioned a lot in current lipid management guidelines in addition to nonpharmacologic approach such as diet and physical exercise.